PROBLEMATIK HUKUM PENERAPAN CURRENCY BOARD SYSTEM DI INDONESIA - Muhammad Excel Suryaprabaswara; . Pujiyono (Jurnal Privat Law, 2023)
This article describes and examines the problem. First, how is the legal problematic if the application of the Currency Board System is carried out in Indonesia. Based on the results of the research, it shows that the problems found are that the Law of the Republic of Indonesia Number 6 of 2009 concerning the Second Amendment to Law Number 23 of 1999 concerning Bank Indonesia and Law Number 24 of 1999 concerning Foreign Exchange Flows and the Exchange Rate System have not accommodated application of the Currency Board System. The law clearly stipulates that Indonesia only adopts a floating exchange rate system. The response from banking law experts calls for the need for a new law and / or amendments to the old law, namely Law of the Republic of Indonesia Number 6 of 2009 concerning the Second Amendment to Law Number 23 of 1999 concerning Bank Indonesia and Law Number 24 of 1999 concerning Foreign Exchange Flows and Exchange Rate System.